WHY SHOULD PUBLIC SERVICE MOTIVATION IMPORTANT FOR VILLAGEDEVELOPMENT - Oldy Arnoldy; Johannes; Edward; Shofia Amin (Bajang Institute, 2021)
The development philosophy by Indonesia is change, starts from the village to correct previous development practices. Hence, public service motivation is essential to promote village development. So, the purpose of this study is to examine the direct and indirect effects of transformational leadership and organizational culture on public service motivation. The methodology accordingly includes a seven-item scale questionnaire survey consisting of 210 samples of village officials. We used the structural model, fit model, and mediation model to test the hypothesis and allow SmartPLS. The result showed that public service motivation is directly influenced by transformational leadership and organizational culture. Indirectly, public service motivation is influenced by transformational leadership mediated by organizational culture. Hence transformational leadership is the essential thing that should be implemented by the village official where they needed to empower. In line with it, organizational culture has a mediation role in improving public service motivation. Hence, the local role of government is expected to empower the village's organizational environment to make the village more positional.